دور التمویل متناھي الصغر في مكافحة الفقر كأحد أھداف إستراتیجیة التنمیة المستدامة في الجزائر - تقییم دور الوكالة الوطنیة لتسییر القرض المصغر في مكافحة الفقر - صالحي, ناجية; بن اعمارة, نوال (جامعة الوادي - University of Eloued, 2015)
The funding issue has imposed itself at both theoretical and applied levels in developing economies,especially with the high rate of poverty and unemployment among different social classes.Which means their incapability for getting capitals for the creation of their own businesses? Consequently, the poverty reality presupposes plans making and policies in order to fight it. Determining a national poverty line has become a necessary step to measure the changes to recognise the scope of the phenomenon, and measuring its intensity in the years to come, micro funding has become among the strategies and policies to eradicate poverty. The international community has made a considerable effort so as to combat poverty as being a strategic goal that everyone is seeking to achieve. Meanwhile, the issue of poverty eradication is in the top of the agenda of the third Millennium development goals, reflecting the aspirations of the nations of the world for a better life a progress towards sustainable development. In this research,
The Role of micro funding in fighting poverty as one of the goals of sustainable development strategy in Algeria -Evaluating the role of the National Agency for micro loan Management in Fighting Poverty
مقال
Keywords: sustainable development, microfinance, micro loan, poverty